Improving methane production from algal sludge based anaerobic digestion by co-pretreatment with ultrasound and zero-valent iron. (10th May 2020) - Li, Lu; Li, Zhouyang; Song, Kang; Gu, Yilu; Gao, Xiaofeng
Abstract: Resource recovery using algal sludge harvested from algal bloom has aroused broad interest. The present study investigated the methane production potential of algal sludge subjected to co-pretreatment with zero-valent iron and ultrasound. Results indicated that the combined zero-valent iron and ultrasound pretreatments induce algal cell wall disruption. Chlorophyll-a concentrations decreased by 14.17%, 25.20%, 35.77%, 45.05%, 61.07%, and 71.52% at zero-valent iron concentrations of 0, 1, 2, 5, 10, and 20 g of zero-valent iron/g of total solid, respectively, after ultrasound treatment for 30 min. Soluble chemical oxygen demands increased 5.22, 8.51, 9.85, 5.52, 11.94, and 9.40 times of corresponding original levels, respectively. After anaerobic digestion for 37 days, accumulative methane production was 30.39, 37.11, 38.06, 42.52, 49.27, 48.93, and 60.84 L CH4 /kg total chemical oxygen demand of algae in Reactors R1–R7, respectively. Methane production constantly increased with zero-valent iron dosage, and the highest methane production was achieved at 20 g of zero-valent iron/g of algal total solid. Methane production in all conditions tested fitted to the one-substrate model. Model analysis indicated that hydrolysis coefficient and the dewaterability of algae increased with zero-valent iron dosage. The present study indicated that a pretreatment method combining zero-valent iron and ultrasound may be developed as an effective resource recovery technology for algal sludge treatment. Graphical abstract: Image 1036 Highlights: ZVI + US co-pretreatment has improved the algae sludge methane production. Algae sludge SCOD has improved 5.22–11.94 times after ZVI + US co-pretreatment. Chl-a of algae sludge has reduced 14.17–71.52% after ZVI + US co-pretreatment. Digested algae sludge dewaterability was improved with ZVI + US co-pretreatment. Algae sludge hydrolysis coefficient increased with the increment of ZVI dosage.